Effects of a training taper on tissue damage indices, serum antioxidant capacity and half-marathon running performance - Child, R. B.; Wilkinson, D. M.; Fallowfield, J. L. (International Journal of Sports Medicine, 2000)
This study investigated the effects of a training taper on muscle damage indices and performance. Two matched groups of seven male runners each performed two self paced half-marathons on a motorised treadmill. After the first half-marathon one group maintained their normal weekly training volume, while the taper group progressively reduced weekly training volume by 85 %. Venous blood was drawn immediately before and after the first half-marathon. Subsequent samples were taken 7 days later, immediately before and after the second half-marathon. Serum samples were analysed for antioxidant capacity, urate concentration and creatine kinase activity (CK). The plasma concentration of malondialdehyde (MDA) was used as a marker of lipid peroxidation. There were no differences in running performance either between the first and second half-marathon within each group, or between groups (86.75 +/- 2.65 min and 87.67 +/- 2.87 min for the "normal training" group vs 85.62 +/- 2.81 min and 85.39 +/- 3.52 min for the "training taper" group). Serum antioxidant capacity and CK were increased over time (P < 0.05, ANOVA), with significant elevations after each half-marathon (P<0.025, t-test). Elevations in MDA attained significance for the first half-marathon (P < 0.05, t-test) when data for both subject groups were pooled. There were no differences in serum antioxidant capacity, or urate concentration between groups. Postexercise CK was lower following the training taper (149 +/- 22% baseline, for the training taper vs 269 +/- 55 % baseline for the normal training group, P<0.05, t-test). Despite evidence that the training taper reduced muscle damage, relative to the normal training group, half-marathon performance was not enhanced.